L’intelligence Emotionelle Chez Les Apprenants De L’ecole Primaire : Cas Du Niveau 6ème Aep (Maroc) - Abid, Mohammed; Bertiaa, Oumzaienb; Belfaquir, Mustapha; Hafid, Mustapha (European Scientific Journal, ESJ, 2016)
At school, the learner is confronted with a group of classmates, peers, rules of life and an environment that generates potential emotions. School is the ideal place to develop the learner’s emotional intelligence. At Moroccan primary schools, learning the emotional intelligence is still underdeveloped, even if professionals and those in charge of education are increasingly aware of its importance. The child is unable to put his emotional life in standby. Without guidance and support, it will be difficult for him to face and handle certain emotions; for instance, those he can experience in the family circle and at school, such as fear before hardships, failure and ridicule. The same applies for timidity before the adult and the group, lack of confidence and, on the contrary, impulsiveness, extroversion, egocentricity, intolerance, aggression, etc. This work of research aims to explore the emotional repertoire of the learners of the 6th AEP (Morocco) in three areas: urban, peri-urban and rural. This study was conducted based on the analysis of the results of a survey consisting of the following five emotional skills: self-consciousness, management of the emotions, relationship with the others, parental relationship and school performance.